Genotype by environment interaction effect on beta-carotene of yellow root cassava (Manihot esculenta Crantz) genotypes in Ghana - Maroya, N.G.; Asante, I.K.; Dixon, A. (International Association of Hydrological Sciences, 2012)
Nine yellow root and one white root cassava genotypes were evaluated in ten environments in Ghana for the variability of their beta carotene content in root. The aim was to identify cassava genotypes that have high beta carotene content in storage root to combat the widespread vitamin A deficiency for children under the age of five years and for pregnant and lactating women. This study was conducted in a Randomized Complete Bloc Design with nine yellow root genotypes namely 01/1224; 01/1235; 01/1368; 01/1371; 01/1412; 01/1417; 01/1442; 01/1610; 01/1663 and one white root cassava namely Wenchi009 as check. In 2005-2006 two experiments were conducted at Wenchi in the Forest-Savannah Transition zone and at Bunso in the Deciduous Forest zone and in 2006-2007, one additional location namely Pokuase in the costal savannah zone was added to Wenchi and Bunso to conduct the same field experiment. Each experiment was harvested two times (9 and 12 or 14 months after planting). At each harvest, beta carotene content analyses were carried out on yellow root cassava at the Nutrition Lab of Noguchi Medical Research Centre using High Performance Liquid Chromatography (HPLC) with a mobile phase made of acetonitrile: dichloromethane: methanol in the ratio 70:20:10 at a flow rate of 2.5 ml/min. Data collected were analyzed using the computer software GenStat Discovery Edition Release 4.2DE; MATMODEL 3.0; GGE biplot. Analyses of results showed statistically significant differences between genotypes for beta carotene content per root, beta carotene content in storage root per plant and but no difference for beta carotene concentration. The best genotype for beta carotene content was 01/1417 follow by 01/1371 and 01/1368.The differences between environments were highly significant for all beta carotene traits. The highest value of beta carotene concentration in fresh root was recorded in environments E , E , E and E . 9 1 7 5 These environments were all characterized by harvest at 9 months after planting. For beta carotene concentration, beta carotene content per storage root and beta carotene content in storage roots per plant the best environments were E (9 9 MAP at Pokuase) and E (9 MAP at Wenchi in 1 2005). The IMMI analysis has shown 01/1412 the most stable for beta carotene concentration. The highest average value of beta carotene content per storage root was registered for genotype 01/1253 followed by 01/1417 and 01/1412. The most stable genotype for beta carotene content per storage root was 01/1610 followed by 01/1371. The highest value was registered for genotype 01/1417 (also the most stable) followed by 01/1368 and 01/1235. Based on the above results the yellow root cassava genotypes 01/1368 and 01/1417 which combined high fresh storage root yield, high dry root yield with high beta carotene content in storage root and in storage root per plant were proposed for on farm testing and released to tackle the vitamin A deficiency in Ghana.